The nursing practice environment and hospital sociotechnical complexity: a mixed-methods study - Riboldi, Caren de Oliveira; Gasparino, Renata Cristina; Wegner, Wiliam; Henriqson, Eder; Saurin, Tarcísio Abreu; Magalhães, Ana Maria Müller de (Revista Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to analyze the relationship between the nursing practice environment and hospital sociotechnical complexity as perceived by nurses. Methods: a sequential explanatory mixed-methods study was conducted in a hospital in southern Brazil. The Brazilian version of the Practice Environment Scale-Nursing Work Index and the Complexity Characterization Questionnaire were administered to 132 nurses. Subsequently, semi-structured interviews were conducted with 18 participants, and the data were subjected to thematic analysis. Data integration was achieved through a connection approach. Results: the nursing practice environment was found to be favorable, except in the subscale concerning Staffing and Resource Adequacy, where complexity was present in the activities. The three emerging categories explained human and technical aspects related to complexity in the practice environment, quality of care, and patient safety. Unexpected variability was inversely correlated with the practice environment. Conclusions: the study results indicate a relationship between these constructs, with implications for the quality and the safety of care. RESUMEN Objetivos: analizar la relación entre el entorno de práctica profesional de enfermería y la complejidad sociotécnica hospitalaria desde la percepción de los enfermeros. Métodos: estudio explicativo secuencial de métodos mixtos realizado en un hospital del sur de Brasil. Se aplicaron la versión brasileña de la Practice Environment Scale-Nursing Work Index y el Cuestionario de Caracterización de la Complejidad a 132 enfermeros. Posteriormente, se realizaron entrevistas semiestructuradas con 18 participantes, sometidas a análisis temático. La integración de los datos se llevó a cabo mediante conexión. Resultados: el entorno de práctica se mostró favorable, excepto en la subescala de Adecuación de personal y recursos, donde se observó complejidad en las actividades. Las tres categorías emergentes explicaron aspectos humanos y técnicos relacionados con la complejidad en el entorno de práctica, la calidad del cuidado y la seguridad del paciente. La variabilidad inesperada se correlacionó inversamente con el entorno de práctica. Conclusiones: los resultados del estudio indican una relación entre estos constructos, con implicaciones para la calidad y la seguridad del cuidado. RESUMO Objetivos: analisar a relação entre o ambiente de prática profissional da enfermagem e a complexidade sociotécnica hospitalar na percepção de enfermeiros. Métodos: estudo explanatório sequencial de métodos mistos realizado em hospital do sul do Brasil. Aplicou-se a versão brasileira da Practice Environment Scale-Nursing Work Index e o Questionário de Caracterização da Complexidade para 132 enfermeiros. Após, realizaram-se entrevistas semiestruturadas com 18 participantes, submetidas à análise temática. A integração dos dados foi por conexão. Resultados: o ambiente de prática revelou-se favorável, exceto na subescala Adequação da equipe e de recursos, e a complexidade presente nas atividades. As três categorias emergentes explicaram aspectos humanos e técnicos, relacionados com a complexidade no ambiente de prática, qualidade do cuidado e segurança do paciente. A variabilidade inesperada correlacionou-se inversamente com o ambiente de prática. Conclusões: os resultados do estudo apontam relação entre os construtos, com implicações para a qualidade e segurança do cuidado.